Consumer Trust in and Emotional Response to Advertisements on Social Media and their Influence on Brand Evaluation - Ivanete Schneider Hahn; Flavia Luciane Scherer; Kenny Basso; Marindia Brachak dos Santos (BBR: Brazilian Business Review)
Social media is becoming an important part of an organization's media strategy. This study examines the effects of trust and consumer emotional response to advertisements on brand evaluation in an online social media context. The study used a survey method, and the studied population consisted of 927 Brazilian social media users (Facebook subscribers). The results showed the following: (1) the emotional response to advertising on social media had a positive influence on brand evaluation; and (2) consumer trust had a positive influence on brand evaluation and emotional response to advertisements on social media. It is possible to conclude that consumer trust is the key variable to a positive emotional response to advertisements on social media and to a positive brand evaluation. Finally, this study demonstrates that companies must measure the emotional response to advertising in their social media activities as a way of enhancing brand evaluation.